New species and records of Paraphloeostiba Steel, 1960 and Xanthonomus Bernhauer, 1926 from the eastern Palaearctic, Oriental and Papuan regions (Coleoptera: Staphylinidae: Omaliinae) - Shavrin, Alexey V. (Zootaxa, 2024)
New taxonomic and faunistic data for nine species of Paraphloeostiba Steel, 1960 and one species of Xanthonomus Bernhauer, 1926 (X. guineensis Shavrin, 2024) from the eastern Palaearctic, Oriental and Papuan regions are provided. Three new species of Paraphloeostiba are described and illustrated: P. acrolochaoides sp. nov. and P. brevicula sp. nov. from Papua New Guinea, and P. zingiberiphila sp. nov. from Malaysia (Sabah). Four species are recorded for the first time: P. gayndanensis (MacLeay, 1873) from Guangxi Province of China, Laos and Japan (Amami-Ōshima), P. papuana (Cameron, 1931) and P. riedeli Shavrin, 2024 from Papua New Guinea, and P. steeli Shavrin, 2024 from Indonesia (Sulawesi).